Biodiversity of Marine Tunicates at Samalona Waters, Sangkarang Archipelago, Indonesia - Litaay, Magdalena; Santosa, Slamet; Johannes, Eva; Agus, Rosana; Moka, Willem; Darmansyah Tanjung, Jennyta Dhewi (Jurnal Ilmu Kelautan SPERMONDE, 2018)
The study aims to know the biodiversity and community structure of marine tunicate of Samalona waters. The present study is part of biodiversity assessment for marine resources of Sangkarang Archipelago SW Makassar Indonesia. Field campaign was conducted from October to November 2016. Sample collection was done at depth of 3 m and 5 m by using Line Intersection Transect (LIT) method combination plot. Two transects size of 50 m were placed parallel to a shore line at three stations (sta.) at Samalona waters. Plot size 2.5 x 2.5 m was placed side by side of transect and all tunicate inside plot was noted, identified, counted and photographed. Sample collection was collected by using SCUBA and under water camera. Environmental parameters including water temperatue, salinity, dissolved oxygen, clarity, current speed, and wind speed were measured in situ. Data were analysed using ecological indices including species composition and density, Shanon Wienner species diversity, Evenness, and Morisita Indices. The result indicates that there are 18 species of tunicates present at depth of 3 m and 7 meters of Samalona waters, respectively. The result of the ecological analysis shows that species diversity is categorized moderate and no dominant species. Environment parameters indicatess that water quality at Samalona waters is in good condition to support tunicates.